INCREASING STUDENTS’ VOCABULARY OF SEVENTH GRADE AT SMP N 1 GALANG THROUGH WORD WALL MEDIA - Inda Indrawati (Jurnal Madako Education, 2017)
The objective of the research is to prove whether word search puzzle can be applied to increase students’ vocabulary. This pre-experimental study uses 22 students as a sample. They are grade VIID of SMP N 1 Galang. The procedure of this research consists of pretest, treatment, and posttest. The result of the analysis shows that word wall media contribute greatly to the students’ vocabulary. It can be seen by the difference of the mean score between pre-test and post-test. The mean score of pre-test was 61.545 while in the post-test improved up to 75.727. The data of this research are analyzed by using SPSS Program version 16.0. Then the data of both tests are analyzed by using T-test, and the result shows that the T-test value 6.172 is high than T-table value 2.831. It can be inferred that word search puzzle was very effective to increase students’ vocabulary.  Keywords:  Increasing, vocabulary, word wall media